ANALYSIS OF THE CONTRAINTS OF CLASSROOM-BASED SPEAKING INTRUCTION: A LITERATURE STUDY - Khairuddin, Khairuddin (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2022)
Ability to speak well in social and professional settings is desired by EFL learners. However, very view have achieved high speaking skill. Hesitation, idea loss, mother tongue interference, word-recalling problems, and low fluency are noticeable stains in their speaking performance. The problems are caused by low self-confidence, reluctant to take risks to speak, and fear of making mistakes and fool of themselves in front of others. In Indonesia context, English speaking practices are mostly done in classroom-based speaking instruction (CBSI). However, CBSI cannot adequately solve those problems. This article aims to reveal the constraints of CBSI through literature analysis. The results showed that CBSI: (1) unable to increase students’ speaking frequency: so many students but so little time, and the teacher takes the biggest portion of the talk; (2) asymmetrical teacher-student interaction: the teacher is more authoritative for his knowledge or status superiority; (3) lack of meaningful communication: the students do not have opportunities to interpret, express, and negotiate meaning in spontaneous oral expression; (4) lack of authentic communication: the purpose of communication is not real but decided by the teacher, not what the students really want to talk about; (5) not promoting autonomous learning. To address the CBSI constraints, English teaching institutions must consider the potential role of ICT such as zoom, Skype, Google meet, podcast, etc., which offer a multitude of ways to engage in communicative activities. The utilization of ICT should be purposed to creating optimal conditions of language learning environment, i.e. opportunities to interact and negotiate meaning, interacting in the target language with authentic audience, involving in authentic tasks, exposure and encouragement to produce varied and creative language, enough time and feedback; guidance to attend mindfully to the learning process, work in an atmosphere with an ideal stress/anxiety level, supporting autonomy.